De heks van Haarlem. Treurspel der onzeekerheid - Eeden, Frederik van 1860-1932 (Amsterdam Versluys, 1915)
At the beginning of the 17th century, Stadholder Frederick Henry is busy laying siege to Antwerp. At the time, the patriotic Cousaert is the bailiff of Haarlem. When he hears from Hille Babbe the fishwife that his son-in-law Arent, a young, wealthy Amsterdam merchant, is supplying arms and ammunition to Antwerp, he must make a choice: betray his son-in-law and thus grieve his daughter Estella or remain silent about this betrayal.
Deals with witch hunts in the 17th century. The play is set in 1638 at the home of the mayor of Haarlem. A divided Europe and a divided Netherlands also divide minds in the mayor's home. Religion and science face each other, as well as collaboration and resistance, and finally inner certainty versus uncertainty.
Written in 1914 in honour of the opening of the Haarlem City Theatre. First performed in Amsterdam february 1915
Keywords: 20th Century (1901-2000); 17th Century (1601-1700); Play (theater); Literature; Witchcraft; Haarlem (Netherlands)